Rab GTPases mature the LC3-associated midbody phagosome. Issue 2 (4th March 2017) - Fazeli, Gholamreza; Wehman, Ann Marie
ABSTRACT: Post-mitotic midbody remnants have recently been added to the list of structures degraded via LC3-associated phagocytosis (LAP). LAP involves proteins of the autophagy pathway to degrade phagosomal contents, mingling 2 pathways that were thought to be distinct. To better characterize how similar LAP is to classical phagocytosis, we asked whether the midbody LAPosome (LC3-associated phagosome) matures using Rab GTPases in C. elegans embryos. We found that RAB-5 and RAB-7 appear transiently on midbody LAPosomes and that RAB-7 is required for midbody degradation, suggesting that RAB-5 and RAB-7 direct LAPosome maturation similar to classical phagosomes. Further, we observed that the Rab2 homolog UNC-108 and the major proton pump, the V-type ATPase, are required for acidification of the midbody LAPosome, demonstrating that phagosomes and LAPosomes acidify via a common pathway. Together, these data reveal that Rab GTPases play similar roles during LAPosome maturation and phagosome maturation.